2021
DOI: 10.1590/fst.13920
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between barley malt protein quantification methods

Abstract: Brazil imports about 60% of all the malt used by the brewing industry which is spread throughout the country. Even though it is an agricultural country, only a small portion of the barley production has the characteristics to produce barley malt for brewing. Seeking supply to the ever-growing demand and reducing the dependency on other countries and logistic costs, malting industries and genetic enhancement companies endeavor to adapt barley to the Brazilian Savannah conditions. For the barley to be malted, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For all‐malt beers, protein values exceeding 12% is the indication of haze formation in beer or present mash runoff problems (Deme et al., 2020). Taking into consideration of the significance of protein in the brewing process, four protein quantification methods, that are, combustion methods—carbon, hydrogen, and nitrogen elemental analysis and Dumas and digestion ones— Kjeldahl and flux injection analysis—were compared and concluded that all quantification methods are valid for determining protein content in barley (Cenci et al., 2020). However, the authors suggested the usage of combustion methods due to their low health and environment hazards and the rapid analysis which takes up to 6 min.…”
Section: Grain: Structure and Morphophysiological Characteristicsmentioning
confidence: 99%
“…For all‐malt beers, protein values exceeding 12% is the indication of haze formation in beer or present mash runoff problems (Deme et al., 2020). Taking into consideration of the significance of protein in the brewing process, four protein quantification methods, that are, combustion methods—carbon, hydrogen, and nitrogen elemental analysis and Dumas and digestion ones— Kjeldahl and flux injection analysis—were compared and concluded that all quantification methods are valid for determining protein content in barley (Cenci et al., 2020). However, the authors suggested the usage of combustion methods due to their low health and environment hazards and the rapid analysis which takes up to 6 min.…”
Section: Grain: Structure and Morphophysiological Characteristicsmentioning
confidence: 99%
“…[9][10][11] At present, there are mainly two methods for detecting protein content in food, namely the Dumas combustion nitrogen method and the Kjeldahl nitrogen method. 12,13 Dumas combustion nitrogen determination: this method uses high-purity oxygen to burn the sample in a hightemperature environment from 900 °C to 1000 °C, producing nitrogen oxides. Other products such as carbon dioxide, sulfur dioxide and water are absorbed by the adsorbent, while nitrogen oxides are reduced to nitrogen gas by tungsten and copper in a reduction tube, and the nitrogen gas is carried by the carrier gas into the thermal conductivity detector to calculate the nitrogen content in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…9–11 At present, there are mainly two methods for detecting protein content in food, namely the Dumas combustion nitrogen method and the Kjeldahl nitrogen method. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods for protein detection, the most commonly used are Kjeldahl method, Lowry method, Dumas method and Bradford method (Bonjoch & Tamayo, 2001;Jiang et al, 2013). It is recommended the use of combustion methods for their lower production of environment-and health-hazardous residues and the rapid analysis (Cenci et al, 2021) .However, the procedure is tedious, the detection takes an extended period of time, and also requires the consumption of large volumes of reagents. Beyond that, Tedious operation also cause damage to the product during the detection (Zhongfu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%